1998
DOI: 10.1210/mend.12.9.0166
|View full text |Cite
|
Sign up to set email alerts
|

BOD (Bcl-2-Related Ovarian Death Gene) Is an Ovarian BH3 Domain-Containing Proapoptotic Bcl-2 Protein Capable of Dimerization with Diverse Antiapoptotic Bcl-2 Members

Abstract: Using the yeast two-hybrid protein-protein interaction system to search for genes capable of forming dimers with the antiapoptotic protein Mcl-1, we have isolated BOD (Bcl-2-related ovarian death agonist) from an ovarian fusion cDNA library. The three variants of BOD (long, medium, and short) have an open reading frame of 196, 110, and 93 amino acids, respectively; all of them contain a consensus Bcl-2 homology 3 (BH3) domain but lack other BH domains found in channel-forming Bcl-2 family proteins. In the yeas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(68 citation statements)
references
References 47 publications
2
65
1
Order By: Relevance
“…21,22 The molecular mechanisms through which BCL-w protein protects cells from ischemic injury remain unclear. However, cell death appears to be regulated partly by competitive interactions between pro-and antiapoptotic Bcl-2-family proteins, [23][24][25] …”
Section: Discussionmentioning
confidence: 99%
“…21,22 The molecular mechanisms through which BCL-w protein protects cells from ischemic injury remain unclear. However, cell death appears to be regulated partly by competitive interactions between pro-and antiapoptotic Bcl-2-family proteins, [23][24][25] …”
Section: Discussionmentioning
confidence: 99%
“…It has three variants (long, medium, and short), all of which contain a consensus BH3 domain without the other BH domains detected in channel-forming Bcl-2 family members. In a yeast cell assay, Hsu et al (1998) found that the C-terminal BH3 domain-containing region of BOD interacted strongly with EBV BHRF1 and all known mammalian anti-apoptotic Bcl-2 proteins (Bcl-2, Bcl-xL, Bcl-w/bcl-2-2, bfl-1, and MCL-1), but not with pro-apoptotic Bcl-2 family proteins (Bok, Bax, Bad, and BAK). While studies on BOD are scarce, northern and southern blot analyses revealed that, unlike Bok, BOD is expressed in various tissues (mainly the spleen and kidney) and has been highly conserved during the evolution of mammals (Hsu et al, 1998).…”
Section: Bhrf1 and Bodmentioning
confidence: 99%
“…Bok interacts only with EBV BHRF1, MCL-1, and bfl-1, but not other pro-apoptotic family members or anti-apoptotic Bcl-2 proteins, unlike other proapoptotic members (BIK, Bax, and BAK) . Moreover, using a direct protein-protein interaction assay in vitro, Hsu et al (1998) demonstrated that Bok-L alone, without Bok-S, interacts strongly with BHRF1. In a variety of cell types, Bok induces cell killing, but this is inhibited following co-expression with BHRF1 and MCL-1, but not with Bcl-2 or Bcl-xL (McCurrach et al, 1997;Rampino et al, 1997;Yin et al, 1997).…”
Section: Bhrf1 and Bokmentioning
confidence: 99%
See 1 more Smart Citation
“…Bim was isolated independently by two groups that exploited its ability to bind Bcl-2 and Mcl1. 20,21 Alternative splicing of Bim gives rise to three variants, BimEL, BimL, and BimS, each of which contains the BH3 domain and functions as a death inducer. In certain cell types, BimEL and BimL, but not BimS, bind to M r ¼8000 dynein light chain, LC8 (also PIN or Dlc-1), 22,23 which negatively regulates the proapoptotic function of the former two isoforms.…”
Section: Introductionmentioning
confidence: 99%